1994
DOI: 10.1111/j.1365-2796.1994.tb00856.x
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and cysteine: determinants of plasma levels in middle‐aged and elderly subjects

Abstract: Age, gender, folate, serum vitamin B12, serum creatinine and multivitamin usage are all important determinants of the plasma homocysteine concentration, whereas only age and serum creatinine are determinants of the plasma cysteine concentration. The age-related increase in homocysteine and cysteine may be linked to the age-related impairment of renal function, whereas the sex difference in plasma homocysteine may be because of the fact that more homocysteine is formed in men than in women in conjunction with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
181
7
6

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(225 citation statements)
references
References 22 publications
31
181
7
6
Order By: Relevance
“…It would seem reasonable to predict an association between tHcy and blood pressure in the general population, given the well described associations between hyperhomocysteinaemia and renal impairment 13 and the postulated effects of homocysteine on vascular endothelial function and proliferation of vascular smooth muscle cells. 3 In the Hordaland Study, a significant positive associations with blood pressure was observed.…”
Section: Homocysteine and Blood Pressurementioning
confidence: 98%
See 2 more Smart Citations
“…It would seem reasonable to predict an association between tHcy and blood pressure in the general population, given the well described associations between hyperhomocysteinaemia and renal impairment 13 and the postulated effects of homocysteine on vascular endothelial function and proliferation of vascular smooth muscle cells. 3 In the Hordaland Study, a significant positive associations with blood pressure was observed.…”
Section: Homocysteine and Blood Pressurementioning
confidence: 98%
“…Homocysteine levels are higher in men than in women and increase with age due to declining renal function. 13 Significant associations are also described with cigarette smoking, serum cholesterol levels and physical inactivity. 14,15 In the Hordarland study, a cross-sectional study of homocysteine and established vascular risk factors, sex, age, folate intake, smoking status and coffee consumption were the strongest determinants of plasma homocysteine concentration in multivariate analysis which did not include serum creatinine.…”
Section: Confoundingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, circulating homocysteine levels are related to plasma creatinine and uric acid concentrations and to sex and age (Brattström et al, 1994;Lussier-Cacan et al, 1996). The gender differences might be reversed when taking into account data obtained during the oral methionine-loading test (Silberberg et al, 1997).…”
Section: Interactions Between Hyperhomocysteinemia and The Usual Riskmentioning
confidence: 99%
“…Brattstrom et al 43 reportaram que a Hcy plasmática e a creatinina sérica se correlacionaram (r = 0,43) em indivíduos idosos do sexo masculino e feminino. Esses autores ainda afirmam que há maior concentração de Hcy nos indivíduos do sexo masculino e que tal diferença pode ser explicada pela relação creatina/creatinina diferente entre os sexos.…”
Section: 2-estudos Com Humanosunclassified